The effect of recreational fitness exercises on sedentary men’s levels of well-being - Muhammet Eyüp Uzuner; Hakan Akdeniz; Müge Sarper; Mehmet Duman; Cengiz Aydin; Talha Altuntaş; Fikret Soyer (Journal of Men's Health, 2025)
Background: Recreation is an indispensable component of leisure time, and physical exercise is one of the most popular recreational activities among sedentary individuals. Regular exercise has positively impacted various health parameters and overall well-being. This study aimed to examine the effect of recreational fitness exercises on the well-being levels of sedentary men. Methods: This experimental study utilized a field trial approach. A total of 200 sedentary men, engaging in fitness exercises for the first time, voluntarily participated in the study. A purposive sampling technique was used in sample selection. The fitness program was implemented 3 days a week for 8 weeks. The Recreational Sport Well-being Scale and demographic information form were used to collect data. The data were analyzed using the SPSS 25.0 package program. The Wilcoxon Signed Ranks Test was used to compare pre- and post-exercise results, with a significance level set at 0.05. Results: Statistically significant differences were observed in physical and mental health (p < 0.01), life satisfaction (p < 0.05) and positive emotion (p < 0.05) sub-dimensions. However, there was no difference in the family relationship development subdimension (p > 0.05). Overall, recreational fitness exercises slightly increased 3 of the 4 components of well-being. Conclusions: The findings suggest that recreational fitness exercises are a valuable intervention for enhancing the well-being of sedentary men. Long-term participation in structured recreational fitness programs may yield more sustained improvements in well-being.